Regenerative cell therapy for the treatment of hyperbilirubinemic Gunn rats with fresh and frozen human induced pluripotent stem cells‐derived hepatic stem cells. (25th July 2019) - Fourrier, Angélique; Delbos, Frédéric; Menoret, Séverine; Collet, Camille; Thi Thuy, Linh Trinh; Myara, Anne; Petit, François; Tolosa, Laia; Laplanche, Sophie; Gómez‐Lechón, María José; Labrune, Philippe; Anegon, Ignacio; et al.
Abstract: Pluripotent stem cells have been investigated as a renewable source of therapeutic hepatic cells, in order to overcome the lack of transplantable donor hepatocytes. Whereas different studies were able to correct hepatic defects in animal models, they focused on the most mature phenotype of hepatocyte‐like cells (HLCs) derived from pluripotent stem cells and needed freshly prepared cells, which limits clinical applications of HLCs. Here, we report the production of hepatic stem cells (pHSCs) from human‐induced pluripotent stem cells (hiPSCs) in xeno‐free, feeder‐free, and chemically defined conditions using as extracellular matrix a recombinant laminin instead of Matrigel, an undefined animal‐derived matrix. Freshly prepared and frozen pHSCs were transplanted via splenic injection in Gunn rats, the animal model for Crigler‐Najjar syndrome. Following cell transplantation and daily immunosuppression treatment, bilirubinemia was significantly decreased (around 30% decrease, P  < .05) and remained stable throughout the 6‐month study. The transplanted pHSCs underwent maturation in vivo to restore the deficient metabolic hepatic function (bilirubin glucuronidation by UGT1A1). In conclusion, we demonstrate for the first time the differentiation of hiPSCs into pHSCs that (a) are produced using a differentiation protocol compatible with Good Manufacturing Practices, (b) can be frozen, and (c) are sufficient to demonstrate in vivo therapeutic efficacy to significantly lower hyperbilirubinemia in a model of inherited liver disease, despite their immature phenotype. Thus, our approach provides major advances toward future clinical applications and would facilitate cell therapy manufacturing from human pluripotent stem cells.